Training and labour market integration of education science graduates - Jiménez Vivas, Amparo [Verfasser] (My University, 2009)
"The aim of the research behind this article is to identify the relationships that must exist between university training and the social and occupational environment. One of the many functions that derive from the universitysociety relationship is to train students to carry out certain professions. As a result, the analysis of the labour market integration of graduates from one university and the definition of their skills becomes a quality indicator of this relationship and one of the pillars that define the list of qualifications within the European Higher Education Area. We therefore look at a range of variables connected with information on professional opportunities, the satisfaction of job expectations, the relationship between university training and professional performance and the assessment of personal, intellectual, vocational and other training received on education science degree courses." (Autorenreferat, BIBB-Doku)
Keywords: S 1.4 Hochschulbildung; L 6 Qualität; P 2.6 Hochschulabsolventen; G 1.2 Arbeitsmarkt; I 2.2.1 Westeuropa; Hochschulbildung; Qualität; Indikatoren; Hochschulabsolvent; Matching; Berufsanforderung; Arbeitsmarkt; Berufsberatung; Spanien